Comparative genomic analysis of Leishmania (Viannia) peruviana and Leishmania (Viannia) braziliensis - Valdivia, Hugo O. (BMC Genomics, 2015)
BACKGROUND: The Leishmania (Viannia) braziliensis complex is responsible for most cases of New World tegumentary leishmaniasis. This complex includes two closely related species but with different geographic distribution and disease phenotypes, L. (V.) peruviana and L. (V.) braziliensis. However, the genetic basis of these differences is not well understood and the status of L. (V.) peruviana as distinct species has been questioned by some. Here we sequenced the genomes of two L. (V.) peruviana isolates (LEM1537 and PAB-4377) using Illumina high throughput sequencing and performed comparative analyses against the L. (V.) braziliensis M2904 reference genome. Comparisons were focused on the detection of Single Nucleotide Polymorphisms (SNPs), insertions and deletions (INDELs), aneuploidy and gene copy number variations. RESULTS: We found 94,070 variants shared by both L. (V.) peruviana isolates (144,079 in PAB-4377 and 136,946 in LEM1537) against the L. (V.) braziliensis M2904 reference genome while only 26,853 variants separated both L. (V.) peruviana genomes. Analysis in coding sequences detected 26,750 SNPs and 1,513 indels shared by both L. (V.) peruviana isolates against L. (V.) braziliensis M2904 and revealed two L. (V.) braziliensis pseudogenes that are likely to have coding potential in L. (V.) peruviana. Chromosomal read density and allele frequency profiling showed a heterogeneous pattern of aneuploidy with an overall disomic tendency in both L. (V.) peruviana isolates, in contrast with a trisomic pattern in the L. (V.) braziliensis M2904 reference. Read depth analysis allowed us to detect more than 368 gene expansions and 14 expanded gene arrays in L. (V.) peruviana, and the likely absence of expanded amastin gene arrays. CONCLUSIONS: The greater numbers of interspecific SNP/indel differences between L. (V.) peruviana and L. (V.) braziliensis and the presence of different gene and chromosome copy number variations support the classification of both organisms as closely related but distinct species. The extensive nucleotide polymorphisms and differences in gene and chromosome copy numbers in L. (V.) peruviana suggests the possibility that these may contribute to some of the unique features of its biology, including a lower pathology and lack of mucosal development. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1928-z) contains supplementary material, which is available to authorized users.